2021
DOI: 10.1007/s00281-021-00861-0
|View full text |Cite
|
Sign up to set email alerts
|

The two facets of gp130 signalling in liver tumorigenesis

Abstract: The liver is a vital organ with multiple functions and a large regenerative capacity. Tumours of the liver are the second most frequently cause of cancer-related death and develop in chronically inflamed livers. IL-6-type cytokines are mediators of inflammation and almost all members signal via the receptor subunit gp130 and the downstream signalling molecule STAT3. We here summarize current knowledge on how gp130 signalling and STAT3 in tumour cells and cells of the tumour micro-environment drives hepatic tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 181 publications
(229 reference statements)
0
5
0
Order By: Relevance
“…Gp130 expression is upregulated in various types of tumors and non-neoplastic liver diseases ( 39 , 40 ). It can be regulated by multiple factors ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gp130 expression is upregulated in various types of tumors and non-neoplastic liver diseases ( 39 , 40 ). It can be regulated by multiple factors ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…In an inflammation-induced liver cancer mouse model, single-cell RNA sequencing analysis (scRNA-seq) revealed that HCC-CCA may originate from hepatic progenitor cells, whose transformation depends on IL-6 secreted by parenchymal and non-parenchymal liver senescent cells via the IL-6-gp130 pathway [152]. gp130 is a common signal-transducing component of the functional receptor complexes for the IL-6 family of cytokines, which can be expressed on the membrane of hepatic progenitor cells [153]. Senescence-induced IL-6 firstly binds to its soluble receptor, gp80, so that it can gain the affinity to be trans-presented to gp130 receptor.…”
Section: Senescence In Cholangiocarcinoma (Cca)mentioning
confidence: 99%
“…Accordingly, it has been shown that the pharmacological inhibition of IL-6 trans-signaling via the administration of recombinant sgp130Fc increased tumor cell survival, proliferation, and migration, suggesting that IL-6 signaling can be associated with a better CCA prognosis [159]. In a carcinoma of the gallbladder (GBC), a CCA-related cancer, downregulation of the soluble receptor, gp80, positively correlated with an improvement in overall survival [153]. Taken together, these data suggest a crucial role of IL-6 in cholangiocarcinoma development, although it must be clarified whether it mainly exerts pro-tumorigenic or anti-tumorigenic functions.…”
Section: Senescence In Cholangiocarcinoma (Cca)mentioning
confidence: 99%
“…It turned out FIGURE 1 | (A) Overview of IL-6 family cytokine receptor complexes. GP130, LIFR, OSMR, and IL-27Rα/WSX-1 are the only receptor subunits of the family that interact with members of the Janus kinase family and are therefore competent for signal transduction (Schmidt-Arras et al, 2021). (B) Trafficking of IL-6 family cytokine receptors.…”
Section: The Interleukin-6 Family Of Cytokinesmentioning
confidence: 99%